Workplace Employee Representation and Industrial Relations Performance: New Evidence from the 2013 European Company Survey - John T. Addison; Paulino Teixeira (Institute of Labor Economics (IZA), 2017)
Using cross-country data from the European Company Survey, we investigate the relationship between workplace employee representation and five behavioral outcomes: strike incidence, the climate of industrial relations, sickness/absenteeism, employee motivation, and staff retention. The evidence is mixed. From one perspective, the expression of collective voice through works councils may be construed as largely beneficial. However, any such optimistic evaluation is heavily qualified by union organization and in particular workplace unionism. Establishment union density seemingly blunts the performance of employee workplace representation, elevating dissatisfaction at the expense of collaboration.
Keywords: J51; J52; J53; J83; 330; employee representation; works councils; union agency; collective bargaining; strikes; industrial relations quality; employee motivation and retention